Flexible Coding of In-depth Interviews: A Twenty-first-century Approach - Deterding, Nicole M.; Waters, Mary C. (Sociological methods & research, 2021)
Qualitative coding procedures emanating from grounded theory were limited by technologies of the 1960s: colored pens, scissors, and index cards. Today, electronic documents can be flexibly stored, retrieved, and cross-referenced using qualitative data analysis (QDA) software. We argue the oft-cited grounded theory framework poorly fits many features of contemporary sociological interview studies, including large samples, coding by teams, and mixed-method analysis. The grounded theory approach also hampers transparency and does not facilitate reanalysis or secondary analysis of interview data. We begin by summarizing grounded theory’s assumptions about coding and analysis. We then analyze published articles from American Sociological Association flagship journals, demonstrating that current conventions for semistructured interview studies depart from the grounded theory framework. Based on experience analyzing interview data, we suggest steps in data organization and analysis to better utilize QDA technology. Our goal is to support rigorous, transparent, and flexible analysis of in-depth interview data. We end by discussing strengths and limitations of our twenty-first-century approach.